Bioethanol as fuel for internal combustion engines - Vladan Mićić; Milovan Jotanović (Zaštita Materijala)
The most promising biofuels are bioethanol, biodiesel, pure plant oil, and biomethane. Many biofuels generate large benefits when compared to fossil fuels. The use of bioethanol will largely depend on the potential of available and continuously re-growing biomass, the feedstock sources. Bioethanol produced from renewable feedstock has great potential to reduce greenhouse gasses emissions related to the combustion of fossil fuels. It has chemical and physical properties that are close to fuels from fossil fuels and can be used to exchange petrol in existing engines. Generally bioethanol is expected to have large socio-economic impacts, especially for local actors. Bioethanol production opens new market opportunities for agricultural products and thus new income options for farmers. In the future agriculture will not only play a role in food production, but also in energy provision.